2000
DOI: 10.1161/01.cir.102.22.2739
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Endothelial Function and Increased Carotid Stiffness in 9-Year-Old Children With Low Birthweight

Abstract: Background-Low birthweight (LBW) has been associated with an increased incidence of adult cardiovascular disease.Endothelial dysfunction and loss of arterial elasticity are early markers of hypertension and atherosclerosis. We studied the prevalence of these markers in 44 healthy, prepubertal (age 9Ϯ1.3 years) children, 22 with LBW for age. Methods and Results-Endothelial function in skin was tested with the local application of acetylcholine (inducing endothelium-dependent vasodilation) and nitroglycerin (end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
205
3
9

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(238 citation statements)
references
References 37 publications
21
205
3
9
Order By: Relevance
“…This combination of iontophoresis and laser Doppler imaging has been used successfully by us and others in Values are medians (interquartile range) a Postcodes were used to obtain the Carstairs deprivation score, which was based on results from the 2001 census. A higher score represents a higher level of deprivation No significant differences in categorical variables using χ 2 or continuous variables using ANOVA were identified SDS, standard deviation score many studies [20,21], and the good reproducibility of the technique has been confirmed [22,23]. A recent study showed that skin microvascular responses to iontophoretically applied ACh strongly correlated with flow-mediated dilatation responses in the brachial artery [24].…”
Section: Methodsmentioning
confidence: 92%
“…This combination of iontophoresis and laser Doppler imaging has been used successfully by us and others in Values are medians (interquartile range) a Postcodes were used to obtain the Carstairs deprivation score, which was based on results from the 2001 census. A higher score represents a higher level of deprivation No significant differences in categorical variables using χ 2 or continuous variables using ANOVA were identified SDS, standard deviation score many studies [20,21], and the good reproducibility of the technique has been confirmed [22,23]. A recent study showed that skin microvascular responses to iontophoretically applied ACh strongly correlated with flow-mediated dilatation responses in the brachial artery [24].…”
Section: Methodsmentioning
confidence: 92%
“…Several studies have shown that endothelial-dependant and -independent vasodilation is impaired and flow-mediated dilation is decreased in low-birthweight individuals at 3 months of age, in later childhood and in early adult life. [63][64][65] In rats that were undernourished during the first 18 days of gestation, increased blood pressure at 60 days after birth was noted, and the maximal vasoconstriction response to phenylephrine and norepinephrine was reduced in isolated femoral arteries, 66 although other maternal nutrient restricted diets 67,68 showed no effect on vasoconstrictor responses.…”
Section: Hypertensionmentioning
confidence: 99%
“…39 Interestingly, the application of sodium nitroprusside causing endothelium-independent vasodilation does not yield differences between children with low and normal birth weight. 40 These findings suggest a crucial role for the endothelium, in particular of the nitric oxide (NO) system. As mechanisms underlying impaired NO-mediated vasodilation increased generation of superoxide and decreased expression of soluble guanylate cyclase have been proposed (Nuyt 1 ; Figure 2).…”
Section: Mechanisms Of Perinatal Programming Of Hypertensionmentioning
confidence: 99%